1993
DOI: 10.1271/bbb.57.1424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyamines on the Ice-nucleating Activity ofErwinia uredovoraKUIN-3

Abstract: The effects ofpolyamines on the ice*nucleating activity of an ice"nucleating bacterium, Erwinia uredovora KUIN-3, were investigated. The activity in the outer membrane derived from this bacterium was increased by the addition of spermidine (lOmM). Also, the activity was stabilized in alkaline pH buffer with the addition of polyamine. Further, the addition of methylglyoxal bis(guanylhydrazone) which inhibited the activity of S-adenosylmethionine decarboxylase, inhibited the ice-nucleating activity of the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Polyamines were extracted using the previously described HCIO4 method (Kawahara et al ., 1993a). The Tosoh polyamine analysis system with the TSKgel Polyaminepak as the analysis column was also used for the analysis and measurement of the polyamines.…”
Section: Extraction and Analysis Of Polyaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines were extracted using the previously described HCIO4 method (Kawahara et al ., 1993a). The Tosoh polyamine analysis system with the TSKgel Polyaminepak as the analysis column was also used for the analysis and measurement of the polyamines.…”
Section: Extraction and Analysis Of Polyaminesmentioning
confidence: 99%
“…The Tosoh polyamine analysis system with the TSKgel Polyaminepak as the analysis column was also used for the analysis and measurement of the polyamines. The conjugated polyamine content in the cell and EIM were estimated using a previously described method (Kawahara et al, 1993a) .…”
Section: Extraction and Analysis Of Polyaminesmentioning
confidence: 99%
“…Various water-soluble substances that inhibit heterogeneous ice nucleation by inactivating INAs have been reported, including some that are biological in origin, and others that are synthetic polymers. ,,− These substances are hereafter referred to in this study as anti-ice nucleating agents (anti-INAs). Anti-INA molecules inactivate INAs by masking ice nucleating sites distributed on the INA surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests the occurence of another possibility that Ina protein molecules act as ice nuclei after they are extracellularly transported into the bulk water phase. lO • l8 ) Kawahara et al 19 ) have reported that E. uredovora, when cultured at a low temperature such as 16°C, sheds Ina matter in the form of a vesicle into the medium. However, it remains unknown whether or not the vesicle contains InaU protein and how the shed vesicle is imparted with ice nucleation activity.…”
mentioning
confidence: 99%
“…To define a relationship between the shedding of the vesicles and the ice nucleation activity, E. uredovora KUIN-3 was grown in TS medium and the vesicles were collected using the previously described method 19) with minor modifications. Briefly, 18 h after the culture at 26°C or 54 h after the culture at 10°C, each medium was centrifuged at 5000 x g for 30 min at 4°C to remove most of t To whom correspondence should be addressed.…”
mentioning
confidence: 99%